2002
DOI: 10.1074/jbc.m110395200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of CCCH Zinc Finger Proteins with mRNA

Abstract: Tristetraprolin (TTP), the prototype of a small family of CCCH tandem zinc finger (TZF) domain proteins, is a physiological stimulator of instability of the mRNAs encoding tumor necrosis factor-␣ and granulocyte/macrophage colony-stimulating factor in certain cell types. TTP stimulates mRNA turnover after binding to class II AU-rich elements (AREs) within the 3-untranslated regions of both mRNAs. In turn, this binding is dependent upon the key CCCH residues in the TZF domain. To evaluate other primary sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
67
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(70 citation statements)
references
References 22 publications
3
67
0
Order By: Relevance
“…Because we did not observe a strict correlation between induction of apoptosis and subcellular localization of TTP (Figures 2b and 3a), we conclude that the TTP Nand C-terminal regions are not required simply to localize the TTP zinc ®ngers, but are involved in interactions or signals that are important for TTP activity. Consistent with this view, expression of TTP zinc ®nger mutants that lack RNA binding activity stabilizes ARE-containing mRNAs, suggesting that these mutants may act as dominant negatives (Lai et al, 2002). In addition, phosphorylation of TTP within regions outside of the zinc ®ngers not only in¯uences TTP subcellular localization (Johnson et al, 2002), but also may inhibit its activity in the cell Zhu et al, 2001).…”
Section: Discussionmentioning
confidence: 48%
“…Because we did not observe a strict correlation between induction of apoptosis and subcellular localization of TTP (Figures 2b and 3a), we conclude that the TTP Nand C-terminal regions are not required simply to localize the TTP zinc ®ngers, but are involved in interactions or signals that are important for TTP activity. Consistent with this view, expression of TTP zinc ®nger mutants that lack RNA binding activity stabilizes ARE-containing mRNAs, suggesting that these mutants may act as dominant negatives (Lai et al, 2002). In addition, phosphorylation of TTP within regions outside of the zinc ®ngers not only in¯uences TTP subcellular localization (Johnson et al, 2002), but also may inhibit its activity in the cell Zhu et al, 2001).…”
Section: Discussionmentioning
confidence: 48%
“…We observed that the first zinc finger mutant of TTP also significantly suppressed NF-B activation with less potency compared with the wild-type TTP protein. Because any zinc finger mutation of TTP protein completely loses its RNA-binding activity (29), our data suggest that the effect of TTP on NF-B signaling may be independent of its RNA-destabilizing activity but that its two zinc fingers may be required for transcription repression.…”
Section: Discussionmentioning
confidence: 91%
“…The solution structure of the TZF domain of ZFP36L2 (TIS11D) bound to the UUAUUUAUU nonamer has been solved (13), providing insight into the interaction between the TZF domain and a target ARE. A core UAUUUAU heptamer unit appears to be necessary for optimal binding affinity of the TZF domain for an ARE (10,14).…”
Section: Tristetraprolin (Ttp)mentioning
confidence: 99%
“…Interactions between the TZF domain and type II AU-rich elements (AREs) found in the 3Ј-untranslated regions (UTRs) of target mRNAs have been the focus of multiple investigations (9 -14). These have included the use of a synthetic TTP TZF domain peptide to examine specificity of ARE target variants (9,11,12), the evaluation of target mRNA decay as it is influenced by mutated TZF domains expressed in co-transfected cells (14), cell-free deadenylation of ARE-containing mRNAs (10,15), and the use of engineered stable transcripts to assess ARE specificity, as measured through mRNA decay (10). The solution structure of the TZF domain of ZFP36L2 (TIS11D) bound to the UUAUUUAUU nonamer has been solved (13), providing insight into the interaction between the TZF domain and a target ARE.…”
Section: Tristetraprolin (Ttp)mentioning
confidence: 99%